The European single market: How far from completion? - Jacques Pelkmans; Monique Goyens; Hans-Peter Burghof; Stephan Leibfried (Intereconomics, 2011)
In 2012, the European Single Market will celebrate its 20th anniversary. Thanks to the May 2010 Monti report and the release of the European Commission's 'Towards a Single Market Act' six months later, renewed scrutiny is being given to the market's achievements and failings over the previous two decades. In this issue's Forum, our authors analyse this progress from diverse viewpoints and draw different conclusions as to the future path to be taken.
Keywords: 330